PENGARUH KONSUMSI RUMAH TANGGA, PENGELUARAN PEMERINTAH DAN PERDAGANGAN INTERNASIONAL TERHADAP PERTUMBUHAN EKONOMI - Husin Husin (Program Studi Akuntansi, 2022)
This study aims to see household consumption, government spending, and international trade have an effect directly and indirectly on the economic growth of Tangerang Regency. This research uses quantitative methods. Using secondary data obtained from data from the Central Statistics Agency. The population is in the form of a household consumption report, government expenditure report, export and import developments, as well as a report on the Gross Regional Domestic Product (GRDP) of Tangerang Regency for 12 years or from 2010 to 2021. Data processing using Smart PLS application version 3.0. The results of hypothesis testing in this study are: (1) Household consumption does not have a significant effect on economic growth with a value of 0.323 < 1.96, (2) Government spending does not have a significant effect on economic growth with a value of 1,930 < 1.96, (3) International trade also has no significant effect on economic growth with a value of 0.729 < 1.96, (4) Household consumption on international trade does not have a significant effect with a value of 1,846 < 1.96, (5) Government spending has no significant effect on international trade with a value of 0.582 < 1.96, (6) There is an insignificant influence between household consumption and economic growth where trade international has no mediation influence with a value of 0.603 < 1.96. (7) There is an insignificant influence between government spending and economic growth where international trade has no mediation influence with a value of 0.233 < 1.96.